Psychometric evaluation of the Psychotic Symptom Rating Scales - Kronmüller, Klaus-Thomas; von Bock, Anique; Grupe, Stefanie; Büche, Liesa; Gentner, Nana Christina; Rückl, Sarah; Marx, Jens Thorsten; Joest, Katharina; Kaiser, Stephan; Vedder, Helmut; Mundt, Christoph (Comprehensive psychiatry, 2011)
Background - The aims of this study were to examine the psychometric properties of a German version of the Psychotic Symptom Rating Scales (PSYRATS) in a sample of patients with schizophrenic spectrum disorders and affective disorders with delusions and to validate subscales of the PSYRATS with other ratings of psychotic symptoms. - Sampling and methods - Two hundred patients with schizophrenic spectrum disorder and affective disorders with delusions were examined. Psychometric properties of the PSYRATS items and scales were determined, and the scores of the PSYRATS scales and subscales were compared to the Positive and Negative Syndrome Scale (PANSS) and other ratings of psychotic symptoms. - Results - The PSYRATS items and scales were found to have excellent interrater reliability. Two factors for the delusions scale (DS) and 4 factors of the auditory hallucinations scale were found. Subscales of the DS and auditory hallucinations scale were replicated by factor analysis, and the validity of the subscales was supported. - Conclusions - The German version of the PSYRATS is a reliable and valid assessment tool for delusions and hallucinations. The findings support the validity of the PSYRATS subscales. The DS is also applicable for patients with affective disorders.
Available online 1 July 2010
Gesehen am 11.07.2022